Kemampuan Menulis Mahasiswa PBJ UNNES Semester 3 Tahun 2019/2020 (Penilaian Kemampuan Berdasarkan JF Standard) - Setiawati, Ai Sumirah (Universitas Negeri Semarang, 2020)
The application of JF Standard in learning Japanese especially in the Sakubun Shochukyu course is new and needs to be evaluated how the achievement of it’s learning targets. This study aims to find out how the semester 3 students' abilities are in writing. The research uses a quantitative approach and the research data are discussed with descriptive techniques. To assess the results of student essays used essay grading rubric based on JF Standard with 4 grading levels namely ganbare, mousukoshi, dekimashita, and subarashii for each item assessed. The results showed that in general, the students' writing ability was in the